An Econometric Analysis of the Determinants of Inflation in Turkey - Papi, Laura (IMF Working Papers; Working Paper, 1997)
High and variable inflation has been a central feature of the Turkish economy since the 1970s. This paper seeks to shed some light on the determinants of inflation in Turkey by analyzing price determination within the framework of a multi-sector macroeconomic model during 1970-95. The main findings are that monetary variables (initially money, more recently the exchange rate) play a central role in the inflationary process, that public sector deficits contribute to inflationary pressures, and that inertial factors are quantitatively important. Policymakers' commitment to active exchange rate depreciation on several occasions in the past 15 years has also contributed to the inflationary process.